Music as strategy of ritualization: an approach to mapuche ritual practice (Per Musi, 2022)
In this article I suggest, based on my ethnographic work and bibliographic discussion, that, due to their emphasis on two massive ceremonies (ngillatun and machitun), studies on Mapuche music have paid little attention to the role of music in daily “ritualized” practices, thus limiting reflection about musical action in ritual contexts only to certain collective ceremonial events. On the contrary, I consider that observing music in various ritual situations can contribute to the understanding of the purposes and agency that sounds and music possess in the Mapuche world. To this end, I propose a way of approaching Mapuche ritual practice —which identifies ritualized practices and collective ritual events— and I consider collective musical action as a strategy of ritualization that is framed within a general dramatization of ritual procedures used on a daily basis.